Existence and Asymptotic Behavior of Ground State Solutions to Kirchhoff-Type Equations of General Convolution Nonlinearity with a Steep Potential Well - Li Zhou; Chuanxi Zhu (Mathematics, 2022)
In this paper, we consider a new kind of Kirchhoff-type equation which is stated in the introduction. Under certain assumptions on potentials, we prove by variational methods that the equation has at least a ground state solution and investigate the asymptotic behavior of solutions.